Understanding the influence of hydrogen on BCC iron grain boundaries using the kinetic activation relaxation technique (k-ART) - Aynour Khosravi; Jun Song; Normand Mousseau (JPhys Materials)
Hydrogen embrittlement (HE) poses a significant challenge to the mechanical integrity of iron and its alloys. This study explores the influence of hydrogen atoms on two distinct grain boundaries (GBs), $Σ37$ and $Σ3$ , in body-centered-cubic (BCC) iron. Using the kinetic activation relaxation technique , an off-lattice kinetic Monte Carlo approach with an EAM-based potential, extensive catalogs of activated events for atoms in both H-free and H-saturated GBs were generated. Studying the diffusion of H, we find that, for these systems, while GB is energetically favorable for H, this element diffuses more slowly at the GBs than in the bulk. The results further indicate that the $Σ 3$ GB exhibits higher stability in its pure form compared to the $Σ 37$ GB, with notable differences in energy barriers and diffusion behaviors. Moreover, with detailed information about the evolution landscape around the GB, we find that the saturation of a GB with hydrogen both stabilizes the GB by shifting barriers associated with Fe diffusion to higher energies and reducing the number of diffusion events. For the $Σ 37$ GB, the presence of hydrogen causes elastic deformation, affecting the diffusion of Fe atoms both at the GB and in adjacent positions. This results in new diffusion pathways but with higher diffusion barriers, unlike for the $Σ 3$ GB. These results indicate that the presence of hydrogen rigidifies the direct GB interface layers while allowing more atoms to be active for the $Σ 37$ GB. This provides a microscopic basis to support the existence of competing mechanisms compatible with either plasticity (such as hydrogen enhanced localized plasticity—HELP) or energy-dominated (hydrogen enhanced decohesion mechanism—HEDE) embrittlement, with the relative importance of these mechanisms determined by the local geometry of the GBs.